Análisis del comportamiento físico-mecánico de una mezcla densa en caliente tipo MDC-2 modificada con caucho y cuero en porcentajes de 25% y 75%, respectivamente (2016)
The goal of this research is to determinate and to analyze the physical and mechanical behavior of one of the most used asphalt mixtures in Colombia, the dense hot mix type MDC-2. A comparison is made of one conventional asphalt mixture with different modified ones via the “wet technique” in different percentages (25% of rubber and 75% of leather). These modifying materials are obtained from wasted materials of the Colombian Military Forces. In addition, the goal is to find out the optimum content of asphalt and modifying materials in order to achieve the best performance and behavior of the mixture when it reaches a dense/hot temperature measuring properties such as strength, deformation and durability. This measurement was done using the Marshall Method which allows the quantification of the most important properties such as the stability, the flow and the Marshall Stiffness.